The Effectiveness of SAVI Learning Model Based on Flipped Classroom on Children's Problem Solving Ability - Happy, Nurina; Mardiati, Mardiati; Hidayati, Nur; Latifah, Nur; Safira, Ifa; Sukini, Sukini; Sarnoto, Ahmad Zain; Sari, Windy Dian; Wantu, Hasyim Mahmud; Nugraha, Aat Ruchiat; Dewanto, Dewanto; Yastanti, Unpris; Santosa, Tomi Apra; Solissa, Everhard Markiano (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effectiveness of the flipped classroom-based SAVI learning model on children's problem-solving skills. This research is a type of meta-analysis research. The eligibility criteria in this study are: a) the research must be published in 2022-2024; b) this research was obtained through the Google Scholar database; Mendeley; ScienceDirect; and Wiley; c) the research must be relevant; d) the research must have complete data to calculate the effect size value; and the sample size > 30 participants. The data in this meta-analysis is analyzed with the help of JASP and Microsoft Excel applications. The results of the analysis of 19 effect sizes concluded that the summary effect size value ( d = 1.077 ; z = 8.172 ; p < 0.001) of the effect size category was strong. These findings show that the application of the effectiveness model of the flipped classroom-based SAVI learning model has a positive influence on children's problem-solving skills